Analisis Determinan Keputusan Transfer Pricing pada Bursa Efek Indonesia - Debbi Chyntia Ovami; Yuni Shara (Jurnal Riset Akuntansi dan Bisnis, 2021)
The purpose of this study was to examine the effect of taxes, foreign ownership and bonus mechanism for transfer pricing decisions in the plantation sector listed on the IDX in 2016-2018. This sample obtained by purposive sampling method using several criteria in order to obtain a sample of 12 companies. Collection Technique the data in this study using documentation techniques. Data analysis technique used is multiple linear regression. The results showed that tax has a positive and insignificant effect on transfer pricing decisions, foreign ownership has a negative effect and significant to the transfer pricing decision, and the bonus mechanism has a positive and significant effect on decisions transfer pricing. And simultaneously tax, foreign ownership, and the bonus mechanism has a significant effect on transfer pricing decisions